The formulation, chemical and physical characterisation of clarithromycin‐based macrolide solution pressurised metered dose inhaler. (11th December 2013) - Saadat, Alessandro; Zhu, Bing; Haghi, Mehra; King, Gregory; Colombo, Gaia; Young, Paul M.; Traini, Daniela
Abstract Objectives The formulation of a clarithromycin (CLA) pressurised metered dose inhalers (pMDIs) solution formulation opens up exciting therapeutic opportunities for the treatment of inflammation in chronic obstructive lung diseases. In this study, we have formulated and tested a low dose macrolide formulation of CLA for treatment of inflammation and studied its physicochemical and aerosol properties. Methods The system was characterised for in‐vitro aerosol performance using an Andersen cascade impactor. Short‐term chemical and physical stability was assessed by dose content uniformity over a range of temperatures. Standard physicochemical characteristics were also investigated using scanning electron microscopy, thermo analysis and laser diffraction techniques. Key findings The formulation had a relatively high fine particle fraction (47%) and produced a particle size distribution suitable for inhalation drug delivery. Particles had an irregular morphology and were predominately amorphous. Furthermore, the short‐term stability showed the formulation to be stable from 4 to 37°C. Conclusions This study demonstrated the feasibility of formulating a solution‐based pMDI containing CLA for the treatment of lung inflammatory diseases.